CHLOROPLAST STRUCTURE AND FUNCTION IN ac-20, A MUTANT STRAIN OF CHLAMYDOMONAS REINHARDI : II. Photosynthetic Electron Transport - Levine, R. P. (The Rockefeller University Press, 1970)
Photosynthetic electron transport is markedly affected in mixotrophic cells of ac-20 because they lack the capacity to form the wild-type level of cytochrome 559, as well as Q, the quencher of fluorescence of photochemical system II. The other components of the electron-transport chain, as well as reactions dependent upon photochemical system I, are unaffected in the mutant strain. These observations are discussed in terms of the previously reported effects of the ac-20 mutation on CO(2) fixation and ribulose-1,5-diphosphate carboxylase activity.